Optical article with a polar coating and its manufacture

CN122953425APending Publication Date: 2026-10-20ESSILOR INTERNATIONAL(COMPAGNIE GENERALE D OPTIQUE)
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202580021756.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-04-04
Filing Date
2025-04-03
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

最后,无论切割深度是多少,来自激光雕刻沟槽的底表面的反射特性都很难接近来自涂层的顶表面的反射特性

Benefits of technology

[0040](21) 用可去除掩模来覆盖该基础元件,该可去除掩模具有与PWG的图案互补的图案;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to an optical article comprising at least: (a) a base element having a front main surface and a rear main surface; (b) a first multilayer interference coating defined as IF1 deposited on at least one region of the front main surface of the base element, the first multilayer interference coating comprising at least one layer having a low refractive index below 1.55 and at least one layer having a high refractive index equal to or greater than 1.55; (c) a coating defined as IF2 comprising a polarization grating, the coating comprising at least one conductive layer, at least one layer having a refractive index below 1.55, and at least one layer having a refractive index equal to or greater than 1.55; wherein the IF2 is deposited on the base element with parallel nanostructure lines of a predetermined pattern protruding from the front surface of the base element, such that linear nanogrooves are formed between different adjacent parallel nanostructure lines, and wherein the IF1 is coated at least on the linear nanogrooves; characterized in that, for an incident angle of 15°, the IF1 and IF2 each have an average light reflectance coefficient Rv in the visible light region. (IF1) and Rv (IF2) , so that |Rv (IF1) - Rv (IF2) | ≤ 0.8%, preferably ≤ 0.7%, particularly ≤ 0.6%, typically ≤ 0.5%, for example ≤ 0.2%, wherein these refractive indices are expressed at a wavelength of 550 nm at 25°C, and wherein the average light reflectance Rv in the visible region is defined in ISO 13666:1998 and measured according to ISO 8980-4.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an optical article comprising a base element, such as a substrate, having a front main surface and a rear main surface, the front main surface being at least partially coated with a coating containing a specific polarization grating and at least partially coated with a multilayer interference coating. This coating combination achieves and / or is configured to provide high transmission polarization efficiency while having controlled reflection characteristics, such as antireflective or specular characteristics. The optical article can be, in particular, an ophthalmic lens, especially a spectacle lens.

[0002] The present invention also relates to a method for manufacturing such an optical article. Background Technology

[0003] Polarizing films block glare caused by light reflection from mirrored surfaces. Polarizing films are widely used in devices such as pocket calculators, watches, word processors, LCD printers, LCD color televisions, and LCD displays in various instruments and automotive dashboards. Furthermore, they are embedded in laminated glass to form anti-glare films for applications such as sunglasses or ski goggles. Polyvinyl alcohol (PVOH) films are commonly used in polarized lens products due to their excellent polarization properties. However, polarizing PVOH films cannot filter wavelengths in incident light that may have adverse effects on general eye health. Iodine and / or dichroic dyes are used in PVOH films to filter a wide range of electromagnetic radiation, but do not provide selective control over wavelengths that may damage the eyes, including blue light in the 415-455 nm range and / or near-infrared (NIR) light in the 700-1400 nm range.

[0004] In the past few decades, another type of polarizing film has been developed for orthogonally polarizing or splitting light, such as wire grid polarizers (WGPs) supported by transparent substrates.

[0005] Specifically, the WGP coating comprises an array of parallel conductive fine lines. These parallel fine lines are characterized firstly by a period or pitch “p” (i.e., the center-to-center distance between two adjacent lines), which is typically less than half the wavelength of the incident light and, typically, less than 150 nm, to provide sufficient bandwidth to cover the visible spectrum. In practice, when the period is much shorter than the wavelength, the wire grid acts as a polarizer, reflecting electromagnetic radiation parallel to the polarization of the fine lines and transmitting orthogonally polarized radiation. The fine lines are also characterized by a width “w” (corresponding to 10% to 90% of the period “p”) and a height “H” (i.e., corresponding to the thickness of the fine lines). Typically, the fine lines are formed of a conductive material.

[0006] A typical wire-grid polarizer (WGP) works as follows. For a light beam generated by a light source, incident at an angle θ to the normal on the polarizer, with the plane of incidence orthogonal to the conductive element, the WGP specifically separates the beam into a specular reflection component and a non-diffractive transmission component. Using the definition of the normal for S-polarization and P-polarization, S-polarized light has a polarization vector orthogonal to the plane of incidence and therefore parallel to the fine line. Conversely, P-polarized light has a polarization vector parallel to the plane of incidence and therefore orthogonal to the conductive line. Typically, a WGP will reflect light whose electric field vector is parallel to the lines of the grid and transmit light whose electric field vector is perpendicular to the lines of the grid, especially when the plane of incidence is perpendicular to the lines of the grid. The geometry chosen here is for clarity. Ideally, the WGP will act as a perfect mirror for one polarization of light (e.g., S-polarized light) and will be completely transparent to the other polarization (e.g., P-polarized light). However, in practice, even the metal wires with the highest reflectivity used as mirrors absorb some of the incident light and reflect only 90% to 95%, and ordinary glass does not transmit 100% of the incident light due to surface reflection.

[0007] Document CN 115903270 describes a film-coated polarizing lens. The lens comprises a substrate having a front main surface and a rear main surface, both surfaces being coated with an abrasion-resistant coating, which itself is coated with a polarizing coating. This polarizing coating is obtained as follows:

[0008] - First, a stack of several material layers is successively deposited by vacuum sputtering, such as an 8-20 nm chromium layer, a 35-45 nm silicon dioxide layer, a 60-110 nm titanium oxide layer, a 35-45 nm silicon dioxide layer, a 100-180 nm titanium oxide layer, and a 60-100 nm silicon dioxide layer.

[0009] - Next, laser engraving is performed on the outermost layer of the stack thus formed to create a pattern of parallel grooves within the thickness of the stack. It has been noted that these grooves have a width of 20 nm and a distance of 20 nm between two adjacent grooves.

[0010] However, the stack in this document does not appear to be based on the principles of interferometric antireflection (AR) or mirror design. For the embodiment where the stack includes a single layer of Cr directly coated on a wear-resistant coating, it is unclear whether the Cr layer is considered part of the interferometric stack. In the embodiment comprising four Cr layers, all Cr layers have the same thickness (20-40 nm), and all internal SiO2 layers have the same thickness (5-15 nm). This is not a typical interferometric AR / mirror design.

[0011] Furthermore, the document makes no mention of the cutting depth within the stack thickness during the engraving process. Therefore, technicians cannot determine which layers are removed by laser engraving. Additionally, if the cutting depth is exactly above the innermost Cr layer, the laser will inevitably cut into at least some distance of the innermost Cr layer's thickness, thus altering its thickness / height, or it will certainly cut into the wear-resistant coating or the substrate. Moreover, regardless of the desired cut, the engraving depth will almost never be uniform. Therefore, the thickness of any remaining layers in the stack that were not removed by laser engraving will be uneven and unreproducible between two lenses that should be identical. Consequently, a lens obtained by the method described in the document is not reproducible on the production line. Finally, regardless of the cutting depth, the reflective properties of the bottom surface from the laser-engraved grooves are rarely comparable to those from the top surface of the coating.

[0012] Furthermore, wire grid polarizers (WGPs), including the parallel conductive fine wire arrays as defined above and as described in document CN 115903270, are susceptible to damage, oxidation, and contamination, which may raise concerns about environmental reliability and make them difficult to apply to ophthalmic lenses.

[0013] Furthermore, for light components with electric field vectors perpendicular to the metal lines, WGP behaves like a dielectric, but for light components with electric field vectors parallel to the lines, WGP behaves like a large block of metal with very high flare reflection. The applicant has observed that laminating WGP films onto ophthalmic lenses provides a prototype of a polarized lens with both very strong forward and backward reflections, which is visually uncomfortable.

[0014] Therefore, the object of the present invention is to provide a new optical article that at least partially avoids the above-mentioned disadvantages and a new method for manufacturing the optical article.

[0015] In practice, there is still a need to provide novel polarizing coatings that have antireflective or reflective properties (i.e., specular) at least in the visible light region, while having good polarization efficiency compared to existing interference coatings.

[0016] Additionally, novel polarizing coatings are needed for optical products (such as ophthalmic lenses) that possess antireflective or reflective properties (i.e., specular) at least in the visible light region, and which have a predetermined perceived color (e.g., hue and chroma C). ), and is repeatable in the production line.

[0017] Novel polarizing coatings that simultaneously possess robust properties and aesthetic appearance (i.e., the intended perceived color) are also required.

[0018] In this invention, the term "robustness" of a polarizing coating is defined as the ability of this polarizing coating to resist changes, regardless of those caused by its manufacturing process. These changes, for example, depend on the type of substrate used, the settings of the manufacturing machine (temperature schedule, appropriate time, electron gun settings, etc.) and / or its usage pattern, or the replacement of said manufacturing machine with another. Robustness is also necessary for lenses with specular coatings (i.e., reflective coatings), which are commonly used in sunglasses. In fact, for specular coatings (and for antireflective coatings), the variability of perceived color from one lens to another can be problematic, especially in a pair of glasses (such as sunglasses) where two individual lenses are placed adjacent to each other. Summary of the Invention

[0019] The applicant seeks to develop a new transparent optical article comprising an organic or mineral-based element with a polarizing stack, preferably a lens, and more preferably an ophthalmic lens for eyeglasses, the polarizing stack having improved polarization efficiency, suitable optical and chromatic properties, and ease of implementation.

[0020] For this purpose, the applicant has developed a novel and atypical structure for optical articles, which includes at least:

[0021] (a) A base element having a front main surface and a rear main surface.

[0022] (b) A first multilayer interference coating defined as IF1, deposited on at least one region of the front primary surface of the base element, the first multilayer interference coating comprising at least one layer having a low refractive index of less than 1.55 and at least one layer having a high refractive index equal to or greater than 1.55.

[0023] (c) A coating defined as IF2 containing a polarization grid, the coating comprising at least one conductive layer, at least one layer having a refractive index less than 1.55, and at least one layer having a refractive index equal to or greater than 1.55.

[0024] The IF2 is deposited on the base element with parallel nanostructure lines of a predetermined pattern protruding from the front surface of the base element, such that linear nanogrooves are formed between different adjacent parallel nanostructure lines, and wherein the IF1 is coated at least on the linear nanogrooves.

[0025] Its characteristic is that, for an incident angle of 15°, IF1 and IF2 respectively have an average light reflectance coefficient Rv in the visible light region. (IF1) and Rv (IF2) , so that |Rv (IF1) - Rv (IF2)| ≤ 0.8%, preferably ≤ 0.7%, particularly ≤ 0.6%, typically ≤ 0.5%, for example ≤ 0.2%,

[0026] These refractive indices are expressed at a wavelength of 550 nm at 25°C.

[0027] Furthermore, the average reflectance coefficient Rv in the visible light region is defined in ISO 13666:1998 and measured according to ISO 8980-4.

[0028] In fact, due to its characteristics, and especially the alternation of IF1 at least entering the nanogroove and IF2 protruding from the front surface of the base element according to a predetermined pattern, and the specific structure of IF2 (that is, where the conductive layer is part of the interference coating), the optical articles of the present invention allow for excellent polarization efficiency while being resistant to damage, oxidation, and contamination. Furthermore, these specific characteristics allow for the acquisition of optical articles with suitable polarization efficiency, as well as antireflective or reflective properties. Additionally, Rv (IF1) With Rv (IF2) Between, h IF1 with h IF2 Between, and C IF1 With C IF2 The very close Rv, hue and C between The value enables the acquisition of optical artifacts that appear uniform to the observer; that is, the prominent parallel nanostructure lines of IF2 are invisible, especially under normal lighting conditions.

[0029] As will be shown below, the optical articles according to the invention are easy to implement and reproducible, which is particularly important for mass production.

[0030] According to the first embodiment, the IF2 is composed of IF1 and a polarization grid coating defined as PWG, the PWG being coated in direct contact over IF1 and having parallel nanostructure lines of a predetermined pattern protruding from the front surface of the base element, and being composed of at least one conductive layer, at least one layer having a refractive index of less than 1.55, and at least one layer having a refractive index equal to or greater than 1.55.

[0031] According to the second embodiment, the IF2 is composed of IF1 and a polarization grid coating defined as PWG, the PWG being coated directly beneath IF1 and having parallel nanostructure lines of a predetermined pattern protruding from the front surface of the base element, and being composed of at least one conductive layer, at least one layer having a refractive index of less than 1.55, and at least one layer having a refractive index equal to or greater than 1.55.

[0032] The present invention also relates to a method for manufacturing an optical article according to the first embodiment described above, the method comprising the following steps:

[0033] (10) Provide basic components;

[0034] (11) Deposit IF1 onto the base element;

[0035] (12) A removable mask is used to cover the base element coated with IF1, the removable mask having a pattern complementary to the pattern of the PWG;

[0036] (13) Deposited PWG;

[0037] (14) Remove the removable mask.

[0038] The present invention also relates to a method for manufacturing an optical article according to the second embodiment described above, the method comprising the following steps:

[0039] (20) Provide basic components;

[0040] (21) The base element is covered with a removable mask having a pattern that is complementary to the pattern of the PWG;

[0041] (22) Deposited PWG;

[0042] (23) Remove the removable mask.

[0043] (24) Deposition of IF1.

[0044] The two methods according to the present invention can produce optical products that are highly robust and easily repeatable in the production line. Attached Figure Description

[0045] To gain a more complete understanding of the descriptions and advantages presented herein, reference is now made to the following brief description in conjunction with the accompanying drawings and detailed description, wherein the same reference numerals denote the same parts.

[0046] Figure 1 This is a schematic cross-sectional view of an optical article according to an embodiment of the present invention (especially those named after the first embodiment);

[0047] Figure 2 This is a schematic cross-sectional view of an optical article according to another embodiment of the present invention (especially those named after the second embodiment);

[0048] Figure 3 This is a schematic cross-sectional view of an optical article according to another embodiment of the present invention (especially those named after the third embodiment);

[0049] Figure 4 This illustrates methods for obtaining optical articles according to the invention, particularly such as... Figure 1 A top view of the different steps involved in the creation of the optical product on display;

[0050] Figure 5 This illustrates another optical article according to the invention, particularly such as... Figure 2 A top view of the different steps involved in the creation of the optical product.

[0051] Figure 6 This is a schematic diagram showing a top view of the front main surface of an optical lens according to a first embodiment, wherein the optical lens is alternately coated with parallel nanostructure lines of IF1 and IF2 in a certain pattern protruding from the front surface, and the remaining portion (hereinafter also referred to as linear nanogrooves) is coated with only IF1. Detailed Implementation

[0052] A) definition

[0053] The terms “comprising” (and any of its grammatical variations, such as “including” and “including”), “having” (and any of its grammatical variations, such as “having” and “possessing”), “containing” (and any of its grammatical variations, such as “containing” and “accommodating”), and “including” (and any of its grammatical variations, such as “containing” and “including”) are all open-ended linking verbs. They are used to specify the presence of the stated feature, whole, step, or component or group thereof, but do not exclude the presence or addition of one or more other features, wholes, steps, or components or groups thereof. Therefore, a method or a step in a method that “comprising,” “having,” “containing,” or “including” one or more steps or elements possesses, but is not limited to, possessing only those one or more steps or elements.

[0054] Unless otherwise specified, all figures or expressions relating to quantities of ingredients, ranges, reaction conditions, etc., used herein should be understood to be modified by the term “about” in all cases.

[0055] Similarly, unless otherwise specified, according to the present invention, the indication of a range of values ​​“X to Y” or “between X and Y” means including values ​​X and Y.

[0056] We mean, but do not exclude, ophthalmic products defined as: corrective lenses, uncorrective lenses, contact lenses, intraocular lenses, magnifying lenses, protective lenses, and goggles containing photochromic compounds in their coatings, lens materials, films, or any adjacent layers.

[0057] As used herein, “base element” may include optical (e.g., ophthalmic) substrates or optical quality support films (i.e., laminates) fixed to optical / ophthalmic substrates by adhesives (e.g., optical quality pressure-sensitive adhesive (PSA layer)).

[0058] As used herein, “interference coating” means a coating that typically consists of an interference thin layer and includes at least one layer with a low refractive index of less than 1.55, defined as a “LI layer”, and at least one layer with a high refractive index of equal to or greater than 1.55, defined as a “HI layer”.

[0059] In this application, when an optical lens includes one or more coatings on its surface, the expression "depositing a layer, sheet or coating onto the article" is intended to mean depositing a layer, sheet or coating onto the outer (exposed) surface of the outer coating of the article, that is, onto the coating furthest from the substrate.

[0060] Unless otherwise specified, a coating, layer, or sheet referred to as being “on” or deposited “on” a substrate / base element is defined as a coating, layer, or sheet that (i) is located above the substrate / base element, (ii) is not necessarily in contact with the substrate / base element, that is, one or more intermediate coatings / sheets may be arranged between the substrate / base element and the coating or sheet in question, and (iii) does not necessarily completely cover the substrate / base element.

[0061] In a preferred embodiment, the coating on or deposited on the substrate / base element is in direct contact with the substrate.

[0062] When “layer / sheet 1 is below layer 2 / sheet 2”, it means that layer / sheet 2 is farther from the substrate than layer 1 / sheet 1.

[0063] The outermost layer or sheet of the interference coating refers to the layer or sheet of the interference coating that is furthest from the substrate.

[0064] The innermost layer or sheet of the interference coating refers to the layer or sheet of the interference coating that is closest to the substrate.

[0065] The inner layer / sheet of the interference coating refers to any layer / sheet of the interference coating other than the outermost layer / sheet of the interference coating.

[0066] Moreover, unless otherwise stated, all thicknesses disclosed in this application refer to physical thicknesses.

[0067] As used herein, the layers of the interference coating are defined as having a thickness greater than or equal to 1 nm. Therefore, when counting the number of layers in the reflective coating, any layer with a thickness less than 1 nm will not be considered. Sublayers (typically having a physical thickness of 150 nm) will also not be considered when counting the number of layers in the interference coating.

[0068] Unless otherwise specified, the refractive index mentioned in this application is expressed at a wavelength of 550 nm at 25°C.

[0069] As used herein, the back (or inner, concave, or CC) surface of the base element / substrate is intended to refer to the surface closest to the wearer's eyes when the article is in use. It is typically concave. Conversely, the front (or convex, or CX) surface of the base element / substrate is the surface furthest from the wearer's eyes when the article is in use. It is typically convex.

[0070] Furthermore, as used herein, “transparent substrate / foundation element” should be understood as transparent when no significant loss of contrast is perceived when viewing an image through the substrate, i.e., when an image is formed through the substrate without adversely affecting the quality of the image.

[0071] The optical products of this invention are compliant with the International Colorimetric System (CIE L). a b The chromaticity coefficients (such as chroma C) in (1976) The hue ("h") is calculated between 380 nm and 780 nm, taking into account the standard illuminant D65 and the observer (at an angle of 10°). The observer is as shown in the International Colorimetric System (CIE L). a b The "standard observer" as defined in CIE L. In fact, in CIE L. a b In space, it can represent not only the overall change in color, but also the change in relation to the parameter L. a and b One or more related changes in L. This can be used to define new parameters and associate them with visual attributes. Clarity related to luminosity is directly determined by L. The value represents chroma. Chroma: C = (a 2 + b 2 ) 1 / 2Chroma is defined. Hue angle: h = arctan(b / a (expressed in degrees); related to hue.

[0072] According to the present invention, colorimetric measurements (reflectance) of a surface (convex / front) coated with the multilayer interference coating of the present invention are performed using a Zeiss spectrophotometer: reflectance coefficient Rv, CIE International Colorimetric Standard (CIE) value (L). , a , b Hue angle h and chroma C in space The standard illuminator D65 and the standard observer 10° (for h and C) are used. (This is taken into account.) They are provided for incident angles of 15° or 35°.

[0073] According to the present invention, the "angle of incidence (symbol θ)" is the angle formed by the light ray incident on the surface of an ophthalmic lens and the normal to the surface at the point of incidence. The light ray is, for example, an illuminant light source, such as those in the International Colorimetric System (CIE L). a b The standard illuminator D65 is defined in (1976). Typically, the angle of incidence varies from 0° (normal incidence) to 90° (grazing incidence). The general range of the angle of incidence is 0° to 75°, and is typically 15° for the present invention.

[0074] Optical properties include at least the average light reflectance R in the visible light region. v Also known as "light reflectivity".

[0075] In this article, "light reflectivity" is denoted as R. v R is defined, for example, in ISO 13666:1998 and measured according to ISO 8980-4, that is, it is the weighted average spectral reflectance over the entire visible spectrum between 380 nm and 780 nm. v Measurements are typically taken for incident angles less than 17°, typically 15°, but can be evaluated for any incident angle. Specifically, for this invention, the Rv of IF1 and IF2 is measured individually and without patterning. In other words, the average light reflectance Rv of a base element coated with IF1 or a base element coated with IF2 without patterning is measured.

[0076] According to the present invention, when the average light reflectance coefficient Rv in the visible light region on the front and / or rear main surfaces of an optical article is strictly greater than 2.5%, more preferably greater than 3%, and even more preferably greater than 5%, this means that the multilayer interference coating can provide specular behavior on the front or rear main surfaces of the optical article, respectively. In particular, "spectral behavior" enables a reduction in transmitted visible, ultraviolet, and / or infrared light. In other words, an optical article having specular behavior on its front main surface reflects at least a portion of the light arriving at said surface. The specular behavior increases light reflection at the article / air interface in a specific portion of the spectrum. The reflection can be in the ultraviolet spectrum, the visible spectrum, or the infrared spectrum.

[0077] According to the present invention, when the average light reflectance R in the visible light region on the front principal surface and / or rear principal surface of the optical article is... v When it is equal to or less than 2.5%, this means that the multilayer interference coating can provide anti-reflection behavior on the front and / or rear main surfaces of the optical article, respectively.

[0078] Moreover, as used herein, consider IF2 to correspond to a coating including a polarization grating coating deposited on the base element in the form of parallel nanostructure lines of a certain pattern protruding from the front surface of the base element, and IF1 to correspond to a first interference coating (excluding any conductive layer) as defined in this set of claims, which is deposited on the base element in the form of a complementary pattern as defined above (i.e., corresponding to the remainder of the main surface of the base element).

[0079] use E represents the relative difference in reflected color between IF1 and IF2, and it is measured as follows:

[0080] Where L IF1 L IF2 a IF1 a IF2 b IF1 b IF2 C IF1 C IF2 These are based on the International Colorimetric System (CIE L). a b For an incident angle of 15°, taking into account the standard illuminator D65, the L of IF1 or IF2 a b C The theoretical value.

[0081] Still use The relative difference in Rv between IF1 and IF2 is measured as follows:

[0082] Among them, Rv IF1 and Rv IF2 These are the average light reflectance coefficients of IF1 and IF2, respectively.

[0083] Furthermore, as used in this paper, the absolute difference of Rv between IF1 and IF2 is defined as The measurements are as follows:

[0084] In this invention, the term "robustness" of an optical article (such as an ophthalmic lens) is defined as the lens's ability to resist changes regardless of those caused by its manufacturing process. For example, these changes depend on the type of substrate / foundation used, the settings of the manufacturing machine (temperature schedule, appropriate time, electron gun settings, etc.) and / or its usage pattern, or the replacement of the manufacturing machine with another.

[0085] Additionally, the polymerization efficiency, defined as PE (%), is calculated as follows: PE(%) = T TM / (T TM + T TE )

[0086] Among them, T TM This refers to the transmittance of TM, where TM is the optical component whose electric field vector is perpendicular to the parallel nanostructure lines of IF2, and T... TE It is the transmittance of TE, which refers to the light component whose electric field vector is parallel to the parallel nanostructure lines of IF2.

[0087] B) Optical articles according to the present invention

[0088] As stated above, the applicant has developed a transparent optical article, particularly an ophthalmic lens, such as a spectacle lens, comprising a base element, such as a mineral or plexiglass substrate, the base element comprising at least a multilayer interference coating, the transparent optical article having improved polarization efficiency, while being comfortable for the user, and not only without compromising the mechanical properties and aesthetic appearance of the optical article, but also without compromising the economic and / or industrial feasibility of its manufacture.

[0089] The optical article is as defined in this set of claims and includes a base element having a front main surface and a rear main surface, the front main surface comprising, in a top view, alternating ribs consisting of a coating comprising at least a polarization grating (defined as IF2) and nanogrooves consisting of a multilayer interference coating (defined as IF1). In particular, IF1 does not include any conductive layer as defined in IF2 and is therefore different from IF2.

[0090] B.1 Basic Components / Substrate

[0091] The optical article according to the present invention includes a basic element.

[0092] According to one embodiment, this base element can be a laminate, that is, an optical quality support film fixed to an optical / ophthalmic substrate by an adhesive (such as an optical quality pressure-sensitive adhesive (PSA layer)). Preferably, the support film is made of cellulose triacetate (TAC) and has a thickness of at least 40 micrometers, preferably in the range of 40 μm to 300 μm (inclusive), and more preferably in the range of 80 μm to 190 μm. The material of the support film can be selected from the group consisting of films made from the following: cellulose triacetate (TAC), cellulose acetate butyrate (CAB), polycarbonate (PC), polyethylene terephthalate (PET), polymethyl methacrylate (PMMA), urethane polymer (TPU), cyclic olefin copolymer (COC), polyester block copolyamide (like Pebax), and polyimide.

[0093] According to another embodiment (described below), the base element may include an ophthalmic substrate of a transparent optical article, such as a lens or lens blank, more preferably an ophthalmic lens or lens blank.

[0094] Generally speaking, the interference coating of the optical article according to the present invention can be deposited on any substrate, and preferably on an organic lens substrate (e.g., a thermoplastic or thermosetting plastic material).

[0095] Thermoplastics may be selected from, for example: polyamides; polyimides; polysulfones; polycarbonates and their copolymers; poly(ethylene terephthalate) and polymethyl methacrylate (PMMA).

[0096] Thermosetting materials can be selected from, for example: cyclic olefin copolymers, such as ethylene / norbornene or ethylene / cyclopentadiene copolymers; homopolymers and copolymers of allyl carbonates of linear or branched aliphatic or aromatic polyols, such as homopolymers of diethylene glycol bis(allyl carbonate) (CR 39). ®(); homopolymers and copolymers of (meth)acrylic acid and its esters derived from bisphenol A; polymers and copolymers of thio(meth)acrylic acid and its esters, polymers and copolymers of allyl esters derived from bisphenol A or phthalic acid and allyl aromatic compounds such as styrene, polymers and copolymers of ethyl carbamate and thioethyl carbamate, polymers and copolymers of epoxy resins, and polymers and copolymers of sulfides, disulfides and cyclic sulfides, and combinations thereof.

[0097] As used herein, (co)polymer is intended to mean copolymer or polymer. As used herein, (meth)acrylate is intended to mean acrylate or methacrylate. As used herein, polycarbonate (PC) is intended to mean homopolymer or copolycarbonate and block copolycarbonate.

[0098] Preferred homopolymers of diethylene glycol bis(allyl carbonate) (CR 39®), allyl and (meth)acrylic acid copolymers with refractive indices between 1.54 and 1.58, polymers and copolymers of ethyl thiocarbamate, and polycarbonate.

[0099] In particular, the recommended base element for use in this invention is a substrate selected from materials obtained by (co)polymerization of di(ethylene glycol) bis(allyl carbonate), and may correspond to CR-39® ESSILOR ORMA® lenses.

[0100] As will be shown below, prior to depositing the antireflective coating of the present invention, the substrate / base element may be coated with one or more functional coatings. These functional coatings, conventionally used in optics, may be, but are not limited to, impact-resistant primers, abrasion-resistant coatings and / or scratch-resistant coatings, polarizing coatings, photochromic coatings, or coloring coatings. In the following, substrate means bare substrate or such coated substrate.

[0101] Preferably, the substrate / base element and the optional abrasion-resistant and / or scratch-resistant coating typically applied to the substrate have similar / close refractive indices to avoid streaks or appearance defects.

[0102] Prior to depositing the interference coating, the surface of the substrate is typically subjected to a physical or chemical surface activation treatment to enhance the adhesion of the antireflective coating. This pretreatment is usually performed under vacuum. It can be bombardment with high-energy and / or reactive substances, such as ion beams (“ion pre-cleaning” or “IPC”) or electron beams, corona discharge treatment, ion spallation treatment, ultraviolet radiation treatment, or vacuum plasma-mediated treatment (typically using oxygen or argon plasma). It can also be an acidic or alkaline treatment and / or a solvent-based treatment (water, hydrogen peroxide, or any organic solvent).

[0103] B.2 Coatings containing polarization gratings (defined as IF2) and multilayer interference coatings (IF1 and IF2)

[0104] As previously described, the base element of the optical article according to the present invention is coated with at least an IF2 consisting of an array of parallel nanostructure lines protruding from its front main surface and a multilayer interference coating IF1, which is coated at least on the remaining portion of the front main surface of the base element.

[0105] In particular, and as described above, the present invention relates to an optical article comprising at least:

[0106] (a) A base element having a front main surface and a rear main surface.

[0107] (b) A first multilayer interference coating defined as IF1, deposited on at least one region of the front primary surface of the base element, the first multilayer interference coating comprising at least one layer having a low refractive index of less than 1.55 and at least one layer having a high refractive index equal to or greater than 1.55.

[0108] (c) A coating defined as IF2 containing a polarization grid, the coating comprising at least one conductive layer, at least one layer having a refractive index less than 1.55, and at least one layer having a refractive index equal to or greater than 1.55.

[0109] The IF2 is deposited on the base element with parallel nanostructure lines of a predetermined pattern protruding from the front surface of the base element, such that linear nanogrooves are formed between different adjacent parallel nanostructure lines, and wherein the IF1 is coated at least on the linear nanogrooves.

[0110] Its characteristic is that, for an incident angle of 15°, IF1 and IF2 respectively have an average light reflectance coefficient Rv in the visible light region. (IF1) and Rv (IF2) , so that |Rv (IF1) - Rv (IF2) | ≤ 0.8%, preferably ≤ 0.7%, particularly ≤ 0.6%, typically ≤ 0.5%, for example ≤ 0.2%,

[0111] These refractive indices are expressed at a wavelength of 550 nm at 25°C.

[0112] Furthermore, the average reflectance coefficient Rv in the visible light region is defined in ISO 13666:1998 and measured according to ISO 8980-4.

[0113] Typically, |Rv (IF1) -Rv (IF2)| ≤ 0.15%, particularly ≤ 0.13%, typically ≤ 0.05%, for example ≤ 0.03%.

[0114] Specifically, the nanogrooves are coated only with IF1.

[0115] The structures of IF1 and IF2 will be described below.

[0116] Therefore, according to the invention, a portion of the front main surface of the base element is coated with IF2, which has a predetermined pattern consisting of an array of parallel nanostructure lines, and another portion, in particular the remainder of the front main surface of the base element (i.e., having a complementary pattern relative to the predetermined pattern defined above), is coated with only IF1.

[0117] IF2 includes at least one conductive layer, at least one layer having a refractive index of less than 1.55 (defined as LI layer) and / or at least one layer having a refractive index equal to or greater than 1.55 (defined as HI layer).

[0118] Preferably, IF2 includes at least one conductive layer with free electrons. This / these layers enable the polarization effect.

[0119] The at least one conductive layer may include one or more of the following components, or may be selected from the group consisting of: chromium, aluminum, silver, gold, copper, indium tin oxide, antimony tin oxide, polythiophene, polyaniline and polyacetylene, and preferably aluminum, silver and / or gold.

[0120] Advantageously, IF2 comprises one to six, preferably one to four, conductive layers. As used herein, “one to six layers” includes the following values ​​and / or any range between these values: 1; 2; 3; 4; 5 and 6.

[0121] According to the characteristics of the invention, in the IF2 coating, all the different conductive layers are independent of each other, if desired. Each conductive layer may have a physical thickness in the range of 4.0 nm to 30 nm, preferably 4.5 nm to 28 nm, and typically 4.5 nm to 25 nm. As used herein, "physical thickness in the range of 3 nm to 30 nm" includes the following values ​​and / or any interval (nm) between these values: 4.0; 4.1; 4.2; 4.3; 4.4; 4.5; 5; 6; 7; 8; 9; 10; 11; 12; 13; 14; 15; 16; 17; 18; 19; 20; 21; 22; 23; 24; 25; 26; 27; 28; 29; 30.

[0122] According to another feature of the invention, the total thickness of all conductive layers is less than or equal to 60 nm, preferably less than or equal to 50 nm, and typically less than or equal to 40 nm. As used herein, "physical thickness less than or equal to 60 nm" includes the following values ​​and / or any range (nm) between these values: 60; 55; 50; 45; 40; 35; 30; 25; 20; 15; 14; 13; 12; 11; 10; 9; 8; 7; 6; 5; 4.5.

[0123] As described above, IF2 further includes a LI layer and / or a HI layer. In particular, this at least one conductive layer is not the layer closest to the base substrate / base element. Specifically, this at least one conductive layer is part of an interference coating consisting of the at least one LI layer and / or the HI layer. Preferably, this at least one conductive layer is positioned between two adjacent layers (each layer can be an HI layer or a LI layer). In other words, this at least one conductive layer can be positioned between a LI layer and an HI layer, between two HI layers, or between two LI layers.

[0124] According to one embodiment of the invention, the other layers of IF2 (i.e., interference layers): (multiple) HI layers and (multiple) LI layers, do not need to alternate with each other in the IF2 coating, but may alternate with each other. Two HI layers (or more) may be deposited one above the other, and two LI layers (or more) may also be deposited one above the other. Typically (but not necessarily), in the IF2 coating according to the invention, these HI layers and LI layers alternate with each other.

[0125] It is a simple stack here because the total number of (multiple) LI layers and / or (multiple) HI layers in IF2 is typically greater than or equal to 2, preferably greater than or equal to 3, particularly greater than or equal to 4, especially greater than or equal to 5, such as greater than or equal to 6. Typically, the total number of (multiple) LI layers and / or (multiple) HI layers is less than or equal to 13, preferably less than or equal to 12, particularly less than or equal to 11, especially less than or equal to 10, such as less than or equal to 9. According to an embodiment, the total number of (multiple) LI layers and / or (multiple) HI layers in IF2 is greater than or equal to 5 and less than or equal to 7.

[0126] Therefore, the total number of layers in IF2 (including at least one conductive layer and at least one HI layer and / or one LI layer) is greater than or equal to 3 layers, preferably greater than or equal to 5 layers, and typically less than or equal to 19 layers, preferably less than or equal to 10 layers.

[0127] The structure of the other LI and HI layers will be described below.

[0128] Typically, the HI layer is a conventional high-refractive-index layer well-known in the art. They typically contain one or more mineral oxides, such as zirconium oxide (ZrO2), titanium oxide (TiO2), titanium pentoxide (Ti3O5), aluminum oxide (Al2O3), tantalum pentoxide (Ta2O5), neodymium oxide (Nd2O5), praseodymium oxide (Pr2O3), praseodymium titanate (PrTiO3), La2O3, Nb2O5, or Y2O3. Optionally, the high-refractive-index layer may also contain silicon dioxide or other low-refractive-index materials, provided that their refractive index is greater than 1.6 as specified above. Preferred materials are TiO2, PrTiO3, ZrO2, Ta2O5, Al2O3, Y2O3, and mixtures thereof. Preferably, the one or more HI layers are made of zirconium oxide (ZrO2).

[0129] The LI layer is also a well-known low-refractive-index layer and may comprise, in a non-limiting manner, silicon oxide, or a mixture of silicon dioxide and alumina, particularly silicon dioxide doped with alumina, which helps to increase the thermal resistance of the UV-reflective interference coating. Each LI layer is preferably a layer containing at least 80% by weight of silicon dioxide relative to the total weight of the layer, and even more preferably at least 90% by weight of silicon dioxide, and even more preferably composed of a silicon dioxide layer (i.e., not obtained by evaporating at least one precursor compound (such as SiO2) in a vacuum chamber using electron beam evaporation with oxygen introduced).

[0130] Optionally, the low-refractive-index layer may also contain a high-refractive-index material, provided that the resulting layer has a refractive index below 1.55. When using a LI layer comprising a mixture of SiO2 and Al2O3, it preferably contains 1% to 10% by weight, more preferably 1% to 8% by weight, and even more preferably 1% to 5% by weight of Al2O3 relative to the total weight of SiO2 + Al2O3 in the layer. For example, SiO2 doped with 4% or less Al2O3 by weight, or SiO2 doped with 8% Al2O3, can be used. Commercially available SiO2 / Al2O3 mixtures can be used, such as LIMA® mixtures (refractive index at 550 nm including n = 1.48-1.50 nm) sold by Umicore Materials AG, or material L5® (refractive index at 500 nm n = 1.48) sold by Merck KGaA.

[0131] In addition, IF2 is characterized by its structure and form.

[0132] In practice, as described above, IF2 is deposited on the base element in the form of a pattern of parallel nanostructure lines protruding from the front surface of the base element. These nanostructure lines typically have a cross-section in the form of a square or rectangle. They are characterized by a pitch defined as “p” (corresponding to the center-to-center distance between two adjacent parallel nanostructure lines), a width defined as “w” (corresponding to the side of the square or the width of the rectangle), and a height defined as “H” (corresponding to the total thickness of IF2, or the side of the square or the length of the rectangle). Figure 1 and Figure 2 These features were demonstrated.

[0133] Typically, "p" is less than or equal to 150 nm, preferably less than or equal to 140 nm, and more preferably less than or equal to 130 nm. Furthermore, according to the characteristics of the invention, "p" is greater than or equal to 90 nm, preferably greater than or equal to 100 nm. As used herein, the range of "less than or equal to 150 nm" includes the following values ​​and / or any interval (nm) between these values: 150; 145; 140; 135; 130; 125; 120; 115; 110; 105; 100; 95; 90.

[0134] Specifically, the height “H” of IF2 is greater than or equal to 100 nm, preferably greater than or equal to 150 nm, particularly greater than or equal to 200 nm, and typically greater than or equal to 215 nm. In particular, “H” is less than or equal to 500 nm, preferably less than or equal to 490 nm, particularly less than or equal to 480 nm, and typically less than or equal to 470 nm.

[0135] Typically, the width “w” of IF2 is in the range of 10% to 90% of the pitch “p” defined above, preferably in the range of 15% to 80%, particularly in the range of 20% to 60%, especially in the range of 40% to 55%, and typically corresponds to 50% of it.

[0136] IF1 comprises at least one layer having a low refractive index below 1.55 (defined as the "LI layer") and at least one layer having a high refractive index equal to or greater than 1.55 (defined as the "HI layer"). In optical articles, the HI and LI layers of IF1 may be the same as (i.e., the same material, the same physical thickness, etc.) or different (i.e., different materials, different thicknesses) the HI and LI layers constituting IF2. In any case, they have the same definition and may be made of the same mineral oxide. Therefore, their description will not be repeated below.

[0137] However, according to the features of the invention, when specular properties (i.e., reflective properties) are required, IF1 may include a thin layer comprising chromium, silicon, and oxygen. This layer is considered a HI layer because it typically has a refractive index equal to or greater than 1.55. Therefore, this thin layer comprising chromium, silicon, and oxygen can be disposed between two LI layers. According to the features of the invention, this thin layer comprising chromium, silicon, and oxygen is positioned directly below the uppermost layer of IF1. Its physical thickness can be less than or equal to 20 nm, more preferably ranging from 1 to 18 nm, and most preferably from 1 to 15 nm. This layer comprising chromium, silicon, and oxygen preferably comprises chromium and silicon oxide, such as SiO or SiO2, more preferably chromium and silicon dioxide (SiO2). The layer preferably comprises 50% to 95% by weight, more preferably 65% ​​to 92% by weight, and most preferably 80% to 90% by weight of silicon oxide (preferably silicon dioxide). The layer preferably contains 5% to 50% by weight, more preferably 8% to 35% by weight, and most preferably 10% to 20% by weight of chromium. Examples of commercially available materials that can be used to form the chromium, silicon, and oxygen-containing layer are Malbunit 8 / 1 (a mixture of SiO2 and Cr) and Flexo (a mixture of SiO and Cr), which are available from Umicore Materials AG.

[0138] IF1 is also a simple stack, because the total number of (multiple) LI layers and / or (multiple) HI layers in IF1 is typically greater than or equal to 2, preferably greater than or equal to 3, particularly greater than or equal to 4, and especially greater than or equal to 5. Typically, the total number of (multiple) LI layers and / or (multiple) HI layers is less than or equal to 10, preferably less than or equal to 9, particularly less than or equal to 8, especially less than or equal to 7, for example less than or equal to 6. According to an embodiment, the total number of (multiple) LI layers and / or (multiple) HI layers in IF1 is greater than or equal to 2 and less than or equal to 4.

[0139] Based on the characteristics of IF1, the innermost layer (i.e., the layer closest to the base element) is the HI layer, such as the ZrO2 layer. Based on another characteristic of IF1, the outermost layer (i.e., the layer farthest from the base element) is the LI layer, such as the SiO2 layer.

[0140] Typically, the HI layer and the LI layer alternate with each other in the IF1 coating according to the present invention.

[0141] Specifically, the total thickness of IF1 can be less than or equal to 250 nm, preferably less than or equal to 230 nm, and typically less than or equal to 220 nm. Furthermore, the total thickness of IF1 can be greater than or equal to 50 nm, preferably greater than or equal to 60 nm, and typically greater than or equal to 70 nm. As used herein, the range of “less than or equal to 250 nm” includes the following values ​​and / or any interval (nm) between these values: 250; 245; 240; 235; 230; 225; 220; 215; 200; 195; 190; 185; 180; 175; 170; 165; 160; 155; 150; 145; 140; 135; 130; 125; 120; 115; 110; 105; 100; 95; 90; 85; 80; 75; 60.

[0142] For example, according to one embodiment, IF1 sequentially includes, starting from a base element / substrate optionally coated with one or more functional coatings:

[0143] (1) The innermost HI layer has a physical thickness of less than or equal to 150 nm, particularly in the range of 50 nm to 140 nm, preferably in the range of 60 nm to 130 nm, and typically in the range of 80 nm to 120 nm, such as 90 nm to 110 nm.

[0144] (2) A LI layer having a physical thickness of less than or equal to 120 nm, particularly ranging from 40 nm to 110 nm, preferably ranging from 45 nm to 105 nm, and typically ranging from 50 nm to 100 nm, such as ranging from 55 nm to 90 nm, such as 60 nm to 80 nm.

[0145] Typically, this exemplary IF1 coating has anti-reflective properties.

[0146] According to another embodiment, IF1 sequentially comprises, starting from a base element / substrate optionally coated with one or more functional coatings:

[0147] (1) A first HI layer having a physical thickness of less than or equal to 60 nm, particularly ranging from 15 nm to 50 nm, preferably ranging from 20 nm to 45 nm, and typically ranging from 25 nm to 40 nm.

[0148] (2) A first LI layer having a physical thickness of less than or equal to 50 nm, particularly ranging from 3 nm to 45 nm, preferably ranging from 5 nm to 40 nm, and typically ranging from 8 nm to 30 nm, for example, ranging from 8 nm to 20 nm.

[0149] (3) A second HI layer having a physical thickness of less than or equal to 110 nm, particularly ranging from 60 nm to 100 nm, preferably ranging from 65 nm to 95 nm, and typically ranging from 70 nm to 90 nm.

[0150] (4) A second LI layer having a physical thickness of less than or equal to 120 nm, particularly ranging from 60 nm to 110 nm, preferably ranging from 65 nm to 100 nm, and typically ranging from 70 nm to 95 nm.

[0151] Similarly, this exemplary IF1 coating has anti-reflective properties.

[0152] According to another embodiment, IF1 sequentially comprises, starting from a base element / substrate optionally coated with one or more functional coatings:

[0153] (1) A first HI layer having a physical thickness of less than or equal to 120 nm, particularly ranging from 70 nm to 120 nm, preferably ranging from 80 nm to 110 nm, and typically ranging from 90 nm to 100 nm.

[0154] (2) A first LI layer having a physical thickness of less than or equal to 60 nm, particularly ranging from 3 nm to 50 nm, preferably ranging from 5 nm to 40 nm, and typically ranging from 8 nm to 30 nm, for example ranging from 10 nm to 25 nm.

[0155] (3) A second HI layer, which is preferably a thin layer comprising chromium, silicon and oxygen, having a physical thickness of less than or equal to 40 nm, particularly ranging from 3 nm to 30 nm, preferably ranging from 5 nm to 25 nm, and typically ranging from 8 nm to 20 nm.

[0156] (4) A second LI layer having a physical thickness of less than or equal to 120 nm, particularly ranging from 60 nm to 110 nm, preferably ranging from 65 nm to 100 nm, and typically ranging from 70 nm to 95 nm.

[0157] This exemplary IF1 coating has reflective properties.

[0158] According to another embodiment, IF1 sequentially comprises, starting from a base element / substrate optionally coated with one or more functional coatings:

[0159] (1) A first HI layer having a physical thickness of less than or equal to 50 nm, particularly ranging from 10 nm to 50 nm, preferably ranging from 13 nm to 45 nm, and typically ranging from 15 nm to 40 nm.

[0160] (2) A first L1 layer having a physical thickness of less than or equal to 70 nm, particularly ranging from 25 nm to 65 nm, preferably ranging from 30 nm to 60 nm, and typically ranging from 35 nm to 55 nm.

[0161] (3) A second HI layer, which is preferably a thin layer comprising chromium, silicon and oxygen, having a physical thickness of less than or equal to 40 nm, particularly ranging from 3 nm to 30 nm, preferably ranging from 5 nm to 25 nm, and typically ranging from 8 nm to 20 nm.

[0162] (4) A second LI layer having a physical thickness of less than or equal to 40 nm, particularly ranging from 3 nm to 30 nm, preferably ranging from 5 nm to 25 nm, and typically ranging from 8 nm to 20 nm.

[0163] This exemplary IF1 coating has reflective properties.

[0164] According to an embodiment (hereinafter referred to as "first embodiment"), IF2 is composed of both IF1 and a polarization grid coating, defined as PWG, which is directly coated on top of IF1 and has parallel nanostructure lines with a predetermined pattern protruding from the front surface of the base element. PWG is composed of at least one conductive layer, at least one layer having a refractive index below 1.55, and at least one layer having a refractive index equal to or greater than 1.55, as described above for IF2. Therefore, according to this embodiment, IF1 is first deposited onto the base element, and then PWG is deposited. Thus, in the portion of the base element including the parallel nanostructure line pattern, there are two consecutive stacks in direct contact (starting from the base element): IF1 and PWG, which together form IF2.

[0165] This embodiment is in Figure 1 The figure shows a base element 1, which includes a front main surface 4 coated with IF1, 2, and an outermost surface 3 of IF1 that is not in contact with the base element 1 coated with PGW, 5 according to a specific pattern.

[0166] Furthermore, according to this specific embodiment, the characteristics of IF1 and PWG are the same as described above and will not be repeated below. Therefore, typically, the pitch "p" (center-to-center distance between two adjacent nanostructure lines 5) and the width "w" ( Figure 1 As shown above, the height "H" of the parallel nanostructure lines protruding from the front surface of the base element (also shown) is as defined above. Figure 1(As shown in the diagram) still corresponds to the height of the PWG as defined above. However, the height of IF2 corresponds to the physical thickness of IF1 + the physical thickness (or height H) of the PWG. These characteristics are defined above and will not be repeated here.

[0167] According to another embodiment (hereinafter referred to as the "Second Embodiment"), IF2 is composed of both IF1 and a polarization gate coating, which is defined as a PWG (described above with respect to the First Embodiment). The PWG is coated directly beneath IF1 and has parallel nanostructure lines with a predetermined pattern protruding from the front surface of the base element. It is composed of at least one conductive layer, at least one layer having a refractive index less than 1.55, and at least one layer having a refractive index equal to or greater than 1.55, as described above for IF2. Therefore, according to this embodiment, and as will be described in more detail below, due to the use of a mask having a pattern complementary to the predetermined pattern in the PWG, the PWG is first deposited onto the base element, and then (after removing the mask) IF1 is deposited. Thus, in the portion of the base element including the parallel nanostructure lines with the predetermined pattern, there are two directly contacting (starting from the base element) successive stacks: PWG and IF1, which together form IF2.

[0168] This embodiment is in Figure 2 The figure illustrates a base element 1 comprising a front main surface 4 of a PGW 5 coated with a specific pattern comprising parallel nanostructure lines protruding from the front main surface 4 of the base element 1. Linear nanogrooves are formed between two adjacent parallel nanostructure lines. IF1 and IF2 are coated into the different nanogrooves thus formed and are also directly coated onto the outermost layer of the PGW 5.

[0169] Furthermore, according to this specific embodiment, the characteristics of IF1 and PWG are the same as described above and will not be repeated below. Therefore, generally, the pitch “p” and width “w” are as defined above. However, the height “H” of the parallel nanostructure lines protruding from the front surface of the base element corresponds here to the height of PWG as defined above + the height of IF1 (also known as the physical thickness). Therefore, the total thickness of IF2 can be less than or equal to 750 nm, preferably less than or equal to 720 nm, and typically less than or equal to 700 nm. Moreover, the total thickness of IF1 can be greater than or equal to 150 nm, preferably greater than or equal to 210 nm, and typically greater than or equal to 270 nm. As used herein, the range of “less than or equal to 750 nm” includes the following values ​​and / or any interval (nm) between these values: 750; 700; 650; 600; 550; 500; 450; 400; 350; 300; 250; 200; 250.

[0170] According to another embodiment (hereinafter referred to as the "Third Embodiment"), IF2 corresponds to PWG. According to this embodiment, the PWG (as defined above) with parallel nanostructure lines having a predetermined pattern is neither positioned below nor above IF1. IF1 is positioned in direct contact within the remaining portion of the front main surface of the base element. In other words, IF1 is disposed within nanogrooves formed between different adjacent parallel nanostructure lines of the PWG.

[0171] In different embodiments, the base element may be pre-coated with one or more functional coatings that are not selected from the interference coating, and IF1 and IF2 (or PWG) are not disposed below the interference coating.

[0172] According to this specific embodiment, the characteristics of IF1 and PWG are the same as those described above and will not be repeated below.

[0173] The optical properties of different coatings according to the present invention will now be described below.

[0174] Their primary characteristic lies in their average light reflectance in the visible light region for an incident angle of 15°.

[0175] Therefore, IF1 and IF2 have average light reflectance coefficients Rv in the visible light region. (IF1) and Rv (IF2) , so that it is defined as = |Rv (IF1) - Rv (IF2) The absolute difference is ≤ 0.8%, preferably ≤ 0.7%, particularly ≤ 0.6%, typically ≤ 0.5%, for example ≤ 0.2%.

[0176] Typically, |Rv (IF1) -Rv (IF2) | ≤ 0.15%, specifically ≤ 0.13%, for example ≤ 0.10%, typically ≤ 0.05%, for example ≤ 0.03%. As used in this article, "absolute difference" "≤ 0.8%" includes the following values ​​and / or any interval (%) between these values: 0.8; 0.79; 0.78; 0.77; 0.76; 0.75; 0.74; 0.73; 0.72; 0.71; 0.70; 0.69; 0.68; 0.67; 0.66; 0.65; 0.64; 0.63; 0.62; 0.61; 0.60; 0.59; 0.58; 0.57; 0.56; 0.55; 0.54; 0.53; 0.52; 0.51; 0.50; 0.49; 0.48; 0.47; 0.46; 0.45; 0.44; 0.4 3; 0.42; 0.41; 0.40; 0.39; 0.38; 0.37; 0.36; 0.35; 0.34; 0.33; 0.32; 0.31; 0.30; 0.29; 0.28; 0.27; 0.26; 0.25; 0.24; 0.23; 0.22; 0.21; 0.20; 0.19; 0.18; 0.17; 0.16; 0.15; 0.14; 0.13; 0.12; 0.11; 0.10; 0.09; 0.08; 0.07; 0.06; 0.05; 0.04; 0.03; 0.02; 0.01; 0.00.

[0177] Furthermore, the relative difference between the average light reflectance coefficients of IF1 and IF2 according to the present invention is as follows: ≤0.2%, preferably ≤0.19%, particularly ≤0.18%, typically ≤0.17%, for example ≤0.15%.

[0178] As used in this article, "absolute difference" "≤ 0.2%" includes the following values ​​and / or any range (%) between these values: 0.20; 0.19; 0.18; 0.17; 0.16; 0.15; 0.14; 0.13; 0.12; 0.11; 0.10; 0.09; 0.08; 0.07; 0.06; 0.05; 0.04; 0.03; 0.02; 0.01; 0.00.

[0179] These properties enable the production of optical articles coated with two interference bands (i.e., IF1 enters the nanogroove and IF2 also defines parallel nanostructure lines coated on IF1, or IF1 enters the nanogroove and IF3 defines parallel nanostructure lines composed of PWG and IF1; or IF1 enters the nanogroove and IF2 defines parallel nanostructure lines) that appear uniform and without peeling to the observer.

[0180] According to an embodiment, for an incident angle of 15°, all the different coatings that constitute the optical article according to the invention can have anti-reflection properties in the visible light region. According to this embodiment, Rv (IF1) and Rv (IF2) Less than or equal to 2.5%, preferably less than or equal to 2.0%, particularly less than or equal to 1.5%, and typically less than or equal to 1.0%. As used herein, “average reflectance Rv in the visible region, ≤ 2.5%” includes the following values ​​and / or any interval (%) between these values: 2.5; 2.4; 2.3; 2.2; 2.1; 2.0; 1.9; 1.8; 1.7; 1.6; 1.5; 1.4; 1.3; 1.2; 1.1; 1.0; 0.9; 0.8; 0.7; 0.6; 0.5; 0.4; 0.3; 0.2; etc.

[0181] According to another embodiment, for an incident angle of 15°, all the different coatings that can constitute the optical article according to the invention can have reflective properties, also known as specular properties, in the visible light region. According to this embodiment, Rv (IF1) and Rv (IF2) Greater than 2.5%, preferably greater than or equal to 2.8%, particularly greater than or equal to 3.0%, and typically less than or equal to 3.5%. As used herein, "average reflectance Rv in the visible region, > "2.5%" includes the following values ​​and / or any range (%) between these values: 2.6; 2.7; 2.8; 2.9; 3.0; 3.1; 3.2; 3.3; 3.4; 3.5; 4.0; 4.5; 5.0; 5.0; 5.5; 6.0; 6.5; 7.0; 7.5; 8.0; 8.5; 9.0; 9.5; 10.0; 3.5; 4.0; 4.5; 5.0; 5.0; 5.5; 6.0; 6.5; 7.0; 7.5; 8.0; 8.5; 9.0; 9.5; 10.0; 10.5; 11.0; 11.0; 11.5; 12.0; 12.5; 13.0; 13.5; 14.0; 14.5; 15.0; etc.

[0182] Furthermore, the different coatings according to the invention are characterized by their chromatic properties, such as their hue (defined as "h") and their chroma (defined as "C"). (”).

[0183] Specifically, for an incident angle of 15°, IF1 and IF2 respectively meet the international colorimetric standard CIE L. a b Chroma C as defined in (1976) :C IF1 C IF2 This makes the chroma C The absolute difference (corresponding to |C) IF1 -C IF2 |) less than or equal to 5, preferably less than or equal to 4, particularly less than or equal to 3, typically less than or equal to 2, for example less than or equal to 1, more preferably less than or equal to 0.5, typically less than or equal to 0.3, for example less than or equal to 0.1, or 0.

[0184] As used in this article, "chroma C" "Absolute difference less than or equal to 5" includes the following values ​​and / or any interval between these values: 5; 4; 3; 2; 1; 0.

[0185] Furthermore, for an incident angle of 15°, IF1 and IF2 respectively meet the international colorimetric standard CIE L. a b The hue angle h defined in (1976) (IF1) h (IF2) This makes the absolute difference of hue "h" (corresponding to |h) (IF1) - h (IF2) |) less than or equal to 10°, preferably less than or equal to 8°, particularly less than or equal to 7°, typically less than or equal to 6°, such as less than or equal to 5°, such as less than or equal to 0.3°, preferably less than or equal to 0.1°, more preferably less than or equal to 0.05°, and even more preferably less than or equal to 0.01°. According to the invention, "the absolute difference of hue "h" is less than or equal to 10°" includes the following values ​​and / or any interval (°) between these values: 10; 9; 8; 7; 6; 5; 4; 3; 2; 1; 0.9; 0.8; 0.7; 0.6; 0.5; 0.4; 0.3; 0.2; 0.1; 0.09; 0.08; 0.07; 0.06; 0.05; 0.04; 0.03; 0.02; 0.01; 0.0.

[0186] In either embodiment, IF1 and IF2 coatings can be prepared without being limited by their hue angle h (0° to 360°), which is related to the residual color displayed by the coating.

[0187] In some embodiments, IF1 and IF2 have hue angles (h) ranging from 15° to 120°, preferably from 25° to 110°, thus making a brownish residual reflection color perceived. In particular, in some embodiments, the IF1 and IF2 coatings have hue angles (h) ranging from 61° to 105°, thereby corresponding to a "yellow" residual reflection color. In some embodiments, the IF1 and IF2 coatings have hue angles (h) greater than or equal to 120°, more preferably greater than or equal to 130°, and even better ranging from 130° to 200°, thus obtaining an interference coating with a green residual reflection color. In particular, in some embodiments, the IF1 and IF2 coatings have hue angles (h) ranging from 106° to 209°, thereby corresponding to a "green" residual reflection color. In some embodiments, the IF1 and IF2 coatings have hue angles (h) ranging from 200° to 300°, preferably from 250° to 280°, thus making a blue residual reflection color perceived. Specifically, in some embodiments, the IF1 and IF2 coatings have a hue angle (h) ranging from 210° to 330°, thereby corresponding to the residual reflective colors of "blue" and derived colors, including more "blue-purple" or even "purple" residual reflective colors. In some embodiments, the IF1 and IF2 coatings have a hue angle (h) ranging from 331° to 60°, thereby corresponding to the residual reflective colors of "red" and derived colors, including "orange," "pink," or "pink gold" residual reflective colors.

[0188] Furthermore, the relative difference in reflective color between different coatings according to the present invention can be such that: IF1- IF2 ≤ 0.15%, preferably ≤ 0.14%, particularly ≤ 0.13%, typically ≤ 0.12%, for example ≤ 0.11% and, for example ≤ 0.10%.

[0189] According to the present invention, "relative difference of reflected color" "Less than or equal to 0.15%" includes the following values ​​and / or any interval (%) between these values: 0.15; 0.14; 0.13; 0.12; 0.11; 0.10; 0.09; 0.08; 0.07; 0.06; 0.05; 0.04; 0.03; 0.02; 0.01; 0.005; 0.0.

[0190] The very close chromaticity characteristics between the different coatings (i.e., IF1 and IF2) that can constitute the optical article of the present invention enable the acquisition of an optical article that appears uniform to the observer. In other words, the nanogrooves coated with IF1 and the nanostructure lines formed with IF2 have very close or similar chromaticity characteristics, making them invisible to the observer under normal lighting conditions.

[0191] These different properties of the coatings (i.e., IF1 and IF2) according to the present invention enable the acquisition of optical articles with excellent polarization efficiency.

[0192] According to the characteristics of the present invention, the transmission polarization efficiency is greater than or equal to 75%, preferably greater than or equal to 80%, particularly greater than or equal to 85%, and especially greater than or equal to 90%.

[0193] According to another aspect of the invention, the total physical thickness of the different interference coatings (IF1, IF2) of the invention is less than or equal to 1 µm, particularly less than or equal to 900 nm, and typically less than or equal to 750 nm.

[0194] As used herein, “thickness less than or equal to 1 µm” includes the following values ​​(in nm) and / or any range between these values ​​(including extreme values): 1000; 950; 900; 850; 800; 790; 780; 770; 760; 750; 740; 730; 720; 710; 700; 690; 680; 670; 660; 650; 640; 630; 620; 610; 600; 590; 580; 570; 560; 550; 540; 530; 520; 510; 500; etc.

[0195] B.3 Other Functional Layers

[0196] In some applications, it is preferred that the main surface of the substrate be coated with one or more functional coatings before depositing the interference coating of the present invention to improve its optical and / or mechanical properties.

[0197] Traditionally, these functional coatings used in optical devices can be, but are not limited to, impact-resistant primer layers, internal abrasion-resistant coatings (also known as hard coatings), antistatic coatings, particularly on concave surfaces of optical articles, or stacks of two or more such coatings. Preferably, ophthalmic lenses do not include photochromic coatings and / or do not include photochromic substrates.

[0198] For example, abrasion-resistant and / or scratch-resistant coatings may be those described in patents FR 2702486 (EP 0614957), US 4 211823, and US 5 015 523. Preferred thermoplastic polyurethane-based primer compositions may be those described in Japanese patents JP 63-141001 and JP 63-87223; poly(meth)acrylic primer compositions may be those described in patent US 5 015 523; thermosetting polyurethane-based compositions may be those described in patent EP 0 404 111; and compositions based on poly(meth)acrylic latex or polyurethane-type latex may be those described in patents US 5 316 791 and EP 0 680 492. Hydrophobic and / or oleophobic coating compositions may include fluorosilanes, such as those described, particularly in patents US 5,081,192, US 5,763,061, US 6,183,872, US 5,739,639, US 5,922,787, US 6,337,235, US 6,277,485, and EP 0933377. A preferred hydrophobic coating is sold by Daikin Industries under the name OPTOOL DSX(R). This relates to fluoropolymers containing perfluoropropylene groups. These functional coatings are well known to those skilled in the art and will not be described in further detail below.

[0199] Typically, optical articles according to the invention, such as ophthalmic lenses, comprise a base element / substrate having, sequentially on its front surface, an impact-resistant primer layer, an abrasion-resistant and / or scratch-resistant layer, an interference coating according to the invention, and a hydrophobic and / or oleophobic coating. Optical articles according to the invention are preferably ophthalmic lenses (spectacle lenses) for a pair of eyeglasses, or ophthalmic lens blanks. The lens may be a polarizing lens, a photochromic lens, or a tinted sunglass lens, optionally providing correction.

[0200] In addition, the back side of the substrate of the optical product (such as an ophthalmic lens) may be successively coated with an impact-resistant primer layer, an abrasion-resistant and / or scratch-resistant layer, a standard interference coating according to the present invention, and a hydrophobic and / or oleophobic coating.

[0201] Preferably, the light absorption rate of the coated article according to the present invention is less than or equal to 50%. Coefficient τ V It should be understood as defined by the international standard (ISO 13666:1998) and measured according to ISO 8980-3. It is defined in the wavelength range of 380 nm to 780 nm.

[0202] C) method

[0203] The present invention also relates to different methods for manufacturing optical articles as defined above.

[0204] According to the embodiments, it is used for manufacturing optical articles, especially according to the first embodiment described above ( Figure 1 The methods for producing optical articles (as shown) include, for example... Figure 4 The following steps are shown:

[0205] (10) Provide basic component 1;

[0206] (11) Deposit IF1, 2 onto the base element 1;

[0207] (12) Cover the base element 1 coated with IF1, 2 with a removable mask 8, the removable mask having a pattern complementary to the pattern of PWG 5;

[0208] (13) Deposited PWG 5;

[0209] (14) Remove removable mask 8.

[0210] In particular, Figure 4 A schematic procedure for manufacturing polar optical articles, such as ophthalmic lenses, is shown. Starting with an HC-coated substrate or base element (step 10), IF1 is first deposited on the lens surface 3 (step 11), and then a mask 8 with the desired nanostructure line pattern is deposited on top of IF1 (2) using advanced nanotechnology (e.g., nanoimprint lithography, inkjet printing, stamping, and any other equivalent technique) (step 12). After masking, an additional layer of PWG 5 is deposited (step 13). Finally, the nanostructure line mask 8 is removed using a suitable solvent (step 14), and then a product with... Figure 5 The image shows a polarized lens with a nanostructured wire pattern. Therefore, a portion of the lens surface (below the masked area) is coated with IF1, while the remaining portion is coated with IF1 + PWG (forming IF2), and the final portion includes metallic nanowires.

[0211] According to the embodiments, it is used for manufacturing optical articles, especially according to the second embodiment described above ( Figure 2 The methods for producing optical articles (as shown) include, for example... Figure 5 The following steps are shown:

[0212] (21) Provide basic component 1;

[0213] (22) Cover the base element 1 with a removable mask 8, which has a pattern complementary to the pattern of PWG 5;

[0214] (23) Deposited PWG 5;

[0215] (24) Remove removable mask 8,

[0216] (25) Deposition of IF1 2.

[0217] In particular, through reference Figure 5 First, a mask 8 with a nanostructured line pattern is deposited on the HC-coated lens surface 3 using advanced nanotechnology as described above (step 21). After masking, PWG is deposited (step 21). Then, a suitable solvent is used to remove the nanostructured line mask 8 (step 22). Finally, IF1 is deposited (step 23). After this procedure, a portion of the lens surface (corresponding to the masked area 8) is coated with IF1, while the remaining portion is coated with PWG + IF1 (forming IF2). Thus, a polarized lens is manufactured.

[0218] Typically, masks used for each of these different methods include one or more of the following commercially available products: Y57-66, SGMI-22, and YNT1 inks.

[0219] Alternatively, the mask can be removed by applying a detergent (such as isopropanol (IPA) and / or methoxypropanol) to the mask.

[0220] As mentioned above, for different methods, masks are deposited by nanoimprint lithography, inkjet printing, stamping, and any other equivalent techniques.

[0221] The layer comprising at least one conductive layer of IF1 and / or PWG is preferably deposited by vapor deposition in a vacuum deposition chamber under vacuum according to any of the following methods:

[0222] i) By vapor deposition, optionally with ion beam assistance;

[0223] ii) By ion beam spraying;

[0224] iii) By cathode sputtering;

[0225] iv) By plasma-assisted chemical vapor deposition.

[0226] These different methods are described in the following references, “Thin Film Processes” and “Thin Film Processes II”, edited by Vossen and Kern, Academic Press, 1978 and 1991, respectively. A particularly recommended method is vacuum deposition. Preferably, the deposition of each of the aforementioned layers is performed by vacuum deposition. This method effectively avoids heating the substrate, which is especially significant for coating heat-sensitive substrates such as plexiglass.

[0227] Naturally, the various embodiments described above for optical articles are also applicable to this method of manufacturing optical articles, and will not be repeated below.

[0228] Example

[0229] A) Characterization

[0230] Optical and colorimetric measurements (reflectance) were performed on the surface of a base element (i.e., the substrate) coated with an exemplary multilayer interference coating (front side) using a spectrophotometer: average reflectance coefficient Rv, CIE International Colorimetric Standard (CIE) value (L). , a , b Hue angle h and chroma C in space The standard illuminator D65 and the standard observer 10° (for h and C) are used. (The following is taken into account.) For forward reflections (Cx surface), they are provided for an incident angle of 15°, and for backward reflections (Cc surface), they are provided for an incident angle of 35°.

[0231] B) General Program

[0232] The ophthalmic lens used in the example includes an MR8® lens with a diameter of 65 mm, a refractive index of 1.60, a refractive power of -2.00, and a thickness of 1.2 mm. Its front surface is coated with an abrasion-resistant and scratch-resistant coating (hard coating) corresponding to a product Mithril® hard coating (Essilor) (refractive index 1.6) with a thickness of 3 µm. Then, according to a specific predetermined pattern, the IF1 and PWG coatings according to the invention are deposited.

[0233] The layers of IF1 and IF1 + PWG (lenses 1 to 15) forming IF2 or PWG + IF1 (lenses 16 to 18) forming IF2 (forming IF2) are deposited by vacuum evaporation (evaporation source: electron gun) without heating the substrate (without introducing oxygen flow).

[0234] The deposition tool is a Satis 1200DLF machine equipped with a Temescal (8 kV) electron gun for evaporating oxides and a (Veeco Mark II) ion gun for the preparative stage (IPC) of preparing the substrate surface with argon ions.

[0235] The thickness of these layers was controlled using a quartz microbalance. Spectroscopic measurements were performed using a Perkin-Elmer lambda 850 spectrophotometer with a variable tilt angle and a universal reflectance accessory (URA).

[0236] C) Test program

[0237] The method for preparing ophthalmic lenses includes introducing a substrate coated with an abrasion-resistant and scratch-resistant coating on its front side into a vacuum deposition chamber, pumping the chamber to obtain a secondary vacuum, activating the surface of the substrate with an argon ion beam (anodine current: 1 A, anodine voltage: 100 V, neutralization current: 130 mA), turning off ion irradiation, depositing individual layers of an IF1 coating and / or PWG onto the substrate by continuous evaporation (as shown in different tables below), and a final ventilation step.

[0238] In particular, for lenses 1 to 15 (according to the first embodiment described above), the following method has been used:

[0239] (10) Provide basic components;

[0240] (11) Deposit IF1 onto the base element;

[0241] (12) Cover the base element coated with IF1 with a removable mask made of SGMI-22 ink, the removable mask having a pattern complementary to the pattern of the PWG.

[0242] (13) Deposited PWG;

[0243] (14) Remove the removable mask by applying isopropyl alcohol (IPA).

[0244] For these examples, the nanostructured wires of PWG have the following properties: p = 100 nm; w = 50 nm; H = as shown in the table below (corresponding to the height of PWG).

[0245] Furthermore, for lenses 16 to 18 (according to the second embodiment described above), the following method has been used:

[0246] (i) Provide basic components;

[0247] (ii) Cover the base element with a removable mask made of SGMI-22 ink, the removable mask having a pattern complementary to the pattern of the PWG;

[0248] (iii) Deposited PWG;

[0249] (iv) Remove the removable mask by applying isopropyl alcohol (IPA).

[0250] (v) Deposition of IF1.

[0251] For these examples, the nanostructured wires of PWG have the following properties: p = 100 nm; w = 50 nm; H = as shown in the table below (PWG + IF1 = IF2).

[0252] Furthermore, the following method has been used for lens 19 (according to the third embodiment described above):

[0253] (i) Provide basic components;

[0254] (ii) Cover the base element with a removable mask having a pattern complementary to the pattern of the PWG;

[0255] (iii) Deposited PWG;

[0256] (iv) Remove the mask.

[0257] (v) Cover the base element with another removable mask having the same pattern as the PWG;

[0258] (vi) Deposit IF1;

[0259] (vii) Remove the other mask

[0260] For this example, the PWG nanostructure wires have the following properties: p = 100 nm; w = 50 nm; H = as shown in the table below (PWG = IF2).

[0261] D) Test lenses and results

[0262] D.1 Lenses 1 to 11 according to the first embodiment of the present invention, wherein IF1 and IF2 have anti-reflective properties.

[0263] Tables 1 to 4 below illustrate the structures, optical and colorimetric properties of different coatings according to the present invention. Table 1 Table 2 Table 3 Table 4

[0264] D.2 Lenses 12 to 15 according to the first embodiment of the present invention, wherein IF1 and IF2 have reflective properties.

[0265] Tables 5 and 6 below illustrate the structures, optical and colorimetric properties of different coatings according to the present invention. Table 5 Table 6

[0266] D.3 The lens 16 according to the second embodiment of the present invention, wherein IF1 and IF2 have anti-reflective properties.

[0267] Table 7 below shows the structure, optical and colorimetric properties of the different coatings IF1 and IF2 according to the present invention. Table 7

[0268] D.4 Lenses 17 and 18 according to the second embodiment of the present invention, wherein IF1 and IF2 have reflective properties.

[0269] Table 8 below shows the structure, optical and colorimetric properties of the different coatings IF1 and IF2 according to the present invention. Table 8

[0270] D.5 Lens 19 according to the third embodiment of the present invention (e.g.) Figure 3 As shown in the figure, IF1 and IF2 have reflective properties.

[0271] Tables 9 to 11 below show the structure, optical and chromatic properties of lens 19; in particular, Tables 9 and 10 show the different coatings IF1 and IF2 of lens 19 according to the invention. Table 11.

Claims

1. An optical article comprising at least: (a) A base element having a front main surface and a rear main surface. (b) A first multilayer interference coating defined as IF1, deposited on at least one region of the front main surface of the base element, the first multilayer interference coating comprising at least one layer having a low refractive index of less than 1.55 and at least one layer having a high refractive index equal to or greater than 1.

55. (c) A coating defined as IF2 containing a polarization grid, said coating comprising at least one conductive layer, at least one layer having a refractive index less than 1.55, and at least one layer having a refractive index equal to or greater than 1.

55. Wherein, IF2 is deposited on the base element with parallel nanostructure lines of a predetermined pattern protruding from the front surface of the base element, such that linear nanogrooves are formed between different adjacent parallel nanostructure lines, and wherein IF1 is coated at least on the linear nanogrooves. Its characteristic is that, for an incident angle of 15°, IF1 and IF2 respectively have an average light reflectance coefficient Rv in the visible light region. (IF1) and Rv (IF2) , so that |Rv (IF1) - Rv (IF2) | ≤ 0.8%, preferably ≤ 0.7%, particularly ≤ 0.6%, typically ≤ 0.5%, for example ≤ 0.2%, The refractive index is expressed at a wavelength of 550 nm at 25°C. Furthermore, the average light reflectance Rv in the visible light region is defined in ISO 13666:1998 and measured according to ISO 8980-4.

2. The optical article according to claim 1, wherein, |Rv (IF1) -Rv (IF2) | ≤ 0.15%, particularly ≤ 0.13%, typically ≤ 0.05%, for example ≤ 0.03%.

3. The optical article according to claim 1 or 2, wherein, The IF2 is composed of both IF1 and a polarization grid coating defined as PWG, which is coated directly on top of IF1 and has parallel nanostructure lines of a predetermined pattern protruding from the front surface of the base element, and is composed of at least one conductive layer, at least one layer having a refractive index of less than 1.55, and at least one layer having a refractive index equal to or greater than 1.

55.

4. The optical article according to claim 1 or 2, wherein, The IF2 is composed of both IF1 and a polarization grid coating defined as PWG, which is coated directly beneath IF1 and has parallel nanostructure lines of a predetermined pattern protruding from the front surface of the base element. It is composed of at least one conductive layer, at least one layer having a refractive index of less than 1.55, and at least one layer having a refractive index equal to or greater than 1.

55.

5. The optical article according to any one of the preceding claims, wherein, For an incident angle of 15°, IF1 and IF2 respectively have the properties specified in the CIE L (International Colorimetric System) standards. a b Chroma C as defined in (1976) :C IF1 C IF2 , so that |C IF1 -C IF2 | Less than or equal to 5, preferably less than or equal to 4, particularly less than or equal to 3, typically less than or equal to 2, more preferably less than or equal to 1, particularly less than or equal to 0.5, typically less than or equal to 0.3, for example less than or equal to 0.

1.

6. The optical article according to any one of the preceding claims, wherein, For an incident angle of 15°, IF1 and IF2 respectively have the properties specified in the CIE L (International Colorimetric System) standards. a b The hue angle h defined in (1976) (IF1) h (IF2) , so that |h (IF1) - h (IF2) | Less than or equal to 10°, preferably less than or equal to 8°, particularly less than or equal to 7°, typically less than or equal to 6°, for example less than or equal to 0.3°, preferably less than or equal to 0.1°, more preferably less than or equal to 0.05°, and even more preferably less than or equal to 0.01°.

7. The optical article according to any one of the preceding claims, wherein, Defined as (T) TM / (T TM + T TE The polarization efficiency of T is greater than or equal to 75%, preferably greater than or equal to 80%, particularly greater than or equal to 85%, especially greater than or equal to 90%, wherein T TM This refers to the transmittance of TM, where TM is the optical component whose electric field vector is perpendicular to the parallel nanostructure lines of IF2, and T... TE It is the transmittance of TE, which refers to the light component of the parallel nanostructure lines whose electric field vector is parallel to IF2.

8. The optical article according to any one of the preceding claims, wherein, IF2 has a pitch, which is defined as "p" and corresponds to the center-to-center distance between two adjacent parallel nanostructure lines. The pitch is less than or equal to 150 nm, preferably less than or equal to 140 nm, preferably less than or equal to 130 nm, and more preferably less than or equal to 110 nm.

9. The optical article according to any one of the preceding claims, wherein, IF2 has a height corresponding to the total physical thickness of the different layers constituting IF2, said height being greater than or equal to 200 nm, preferably greater than or equal to 250 nm, particularly greater than or equal to 300 nm, and typically greater than or equal to 350 nm.

10. The optical article according to any one of the preceding claims, wherein, The parallel nanostructure lines are identical and have a width defined as w, which is in the range of 10% to 90% of the pitch as defined in claim 8, preferably in the range of 15% to 80%, particularly in the range of 20% to 60%, especially in the range of 40% to 55%, and typically 50% of it.

11. The optical article according to claim 3 or 4, in combination with any one of claims 5 to 10, wherein, The PWG comprises one to six, preferably one to four, conductive layers. In particular, the physical thickness of each conductive layer is in the range of 4.5 nm to 30 nm, preferably 4.5 nm to 28 nm, and typically 4.5 nm to 25 nm. Advantageously, the total thickness of all conductive layers is less than or equal to 80 nm, preferably less than or equal to 70 nm, and typically less than or equal to 50 nm.

12. The optical article according to any one of claims 1 to 11, wherein, For an incident angle of 15°, Rv (IF1) and Rv (IF2) Less than or equal to 2.5%, preferably less than or equal to 2.0%, particularly less than or equal to 1.5%, and typically less than or equal to 1.0%. or Rv (IF1) and Rv (IF2) Greater than 2.5%, preferably greater than or equal to 3.0%, particularly greater than or equal to 3.5%, and typically greater than or equal to 4.0%.

13. A method for manufacturing an optical article according to any one of claims 3 to 12, comprising the following steps: (10) Provide the aforementioned basic components; (11) Deposit IF1 onto the base element; (12) The base element coated with IF1 is covered with a removable mask having a pattern complementary to the pattern of the PWG. (13) Deposited PWG; (14) Remove the removable mask.

14. A method for manufacturing an optical article according to any one of claims 4 to 12, comprising the following steps: (20) Provide the aforementioned basic components; (21) The base element is covered with a removable mask having a pattern complementary to the pattern of the PWG; (22) Deposited PWG; (23) Remove the removable mask; (24) Deposition of IF1.

15. The method according to claim 13 or 14, wherein, The mask is applied to the base element, which may or may not be coated with IF1, by nanoimprint lithography, inkjet printing, or stamping.

Citation Information

Patent Citations

  • Process for producing plastic lens

    EP0404111A2

  • Abrasion-resistant coating compositions containing hydrolised silanes and aluminium compounds; coated articles resistant to abrasion and shocks

    EP0614957A1

  • Process for improving impact resistance of coated plastic substrates

    EP0680492A1

  • Anti-smudge agent, method of forming an anti-smudge layer, anti-reflection optical member and display device

    EP0933377A2

  • Plastic lens and its manufacture

    JP1988087223A